Phosphorus Fertilizer Recommendations for Sugarcane on Florida Mineral Soils - J. Mabry McCray (EDIS, 2022)
This presents phosphorus fertilizer recommendations for sugarcane produced for sugar on Florida mineral soils along with supporting information. Written by J. Mabry McCray, and published by the UF/IFAS Agronomy Department, August 2022.